PENGARUH ENDORSE SELEBRITIS, HARGA DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA ANGGOTA POLWAN DI POLDA KALIMANTAN BARAT - Noviyantika, Noviyantika; Diana, Tri (Universitas Muhammadiyah Parepare, 2021)
The growing number of online shops pushes women, especially Policewomen of Local Police in West Kalimantan easier to buy all the necessities without having to leave the house or office. One of the reasons that cause online shopping is a lifestyle choice that suits the Policewomen of Local Police in West Kalimantan is; a policewoman knows they are busy and should be active at the office that makes them difficult to find time for shopping outside the office. Frequently, the products purchased by the Policewomen of Local Police in West Kalimantan were food, clothing, shoes, bags, cosmetics, and others. Many factors influence the decision of the Policewomen of Local Police in West Kalimantan to purchase, including celebrity endorsers, price, and convenience. The purpose of this research are to determine whether there is an influence of celebrity endorsements on online purchasing decisions toward the Policewomen of Local Police in West Kalimantan and to determine whether there is an influence of price on online purchasing decisions toward the Policewomen of Local Police in West Kalimantan as well to determine whether there is an influence of convenience on online purchasing decisions toward the Policewomen of Local Police in West Kalimantan. The research method was a survey. Data collection techniques: interviews, questionnaires, and documentary studies. The sample in this research were policewomen who are active in using social media and have shopped online on social media or other shopping sites so that they are more representative, amounting to 100 people in 2020 with the accidental sampling technique. The results showed from data analysis that carried out by regression doubled displayed there was an influence of celebrity endorsement, price, and convenience toward the decision of online purchases for the Policewomen of Local Police in West Kalimantan.